Long-term follow-up analysis of zolpidem in fingernails after a single oral dose - Hang, Chen; Ping, Xiang; Min, Shen (Analytical and bioanalytical chemistry, 2013)
The determination of xenobiotics in keratinized matrices, such as nails and hair, has received considerable attention because of the relatively long detection window for compounds. The distribution of xenobiotics in fingernails, unlike hair, was equivocal. The main aim of this study was to use follow-up surveys to measure zolpidem profiles in nails after subjects consumed a single dose of the drug. In addition, the zolpidem concentrations in nails were compared with data for different biosamples, such as hair and blood from previous work. With these preconditions, a high-performance liquid chromatography–tandem mass spectrometry method was developed and validated for the determination of zolpidem in nails. Nails underwent alkaline hydrolysis and were extracted with diethyl ether. A Capcell Pak C18 MGII column was used to separate the target compound, and an API 4000 Qtrap mass spectrometer was used as a detector. The results for nail samples from seven subjects who had taken a single 10 mg zolpidem dose were significant: two relatively high zolpidem concentrations were observed in the long-term follow-up analysis of nails. The zolpidem concentration was less than 1.74 pg/mg and less than 3.29 pg/mg in fingernails and toenails, respectively. The subsequent peak concentration of zolpidem was observed between 10 and 15 weeks after each subject took a single dose of the drug. This result suggested that the germinal matrix area was a primary in vivo pathway for zolpidem secretion into the nail. The analysis of biosamples, such as nails, may be a useful adjunct to conventional methods of drug testing and hair analysis. Further research is needed concerning the contamination risk in analysis of nail biosamples.